Technology for men and women: Recommendations to reinforce gender mainstreaming in agricultural technology innovation processes for food security - Polar, Vivian; Babini, C.; Flores, P. (International Potato Center, 2015)
The main objective of this study is to contribute to the mainstreaming of gender in the design, implementation and monitoring of interventions on agricultural innovation for food security. This work was developed from an analysis of the experience of the project “Strengthening pro-poor agricultural innovation for food security in the Andean region” IssAndes, implemented by the International Potato Center and funded by the European Commission’s Thematic Program on Food and Nutrition Security and Sustainable Agriculture, through the International Fund for Agricultural Development.